Participant satisfaction with Youth Justice Conferencing - Bianca Blanch
Aims: To evaluate offender and victim satisfaction with New South Wales (NSW) Youth Justice Conferences (YJCs) immediately after conference participation and to re-assess victim satisfaction 4 months after the conference date.Method: A self-report survey designed to assess satisfaction with YJCs was completed by 263 offenders and 141 victims immediately following their participation in a NSW YJC. Additionally, 96 victims also participated in a phone-based survey 4 months after the conference.Results: When asked immediately following the conference, more than 85 per cent of offenders and victims reported being ‘satisfied’ or ‘very satisfied’ with most aspects of the conference. High levels of satisfaction with conferencing were also reported by victims 4 months after the conference. For some measures, however, the percentage of victims who were ‘satisfied’ or ‘very satisfied’ was not as high at the 4-month follow-up, as it was in the baseline survey. The aspect of conferencing that victims at the 4-month follow-up reported the least satisfaction with was the lack of feedback they received from conference staff about the offender’s completion of the outcome plan. Fewer than half of the victims were ‘satisfied’ or ‘very satisfied’ with this part of the conference.Conclusion: The results of this study suggest that offender and victim satisfaction is high immediately following a YJC. Even 4 months after a YJC, victim satisfaction with most aspects of conferencing remains high. Satisfaction levels may be increased still further if, at some point prior to the end of the statutory time-period for completing the plan, victims were provided with feedback about the offender’s progress towards completing the outcome plan. Further research also needs to be conducted comparing victim satisfaction following a conference with victim satisfaction following a court appearance